Tamoxifen triggers the in vitro release of neutrophil extracellular traps in healthy horses - Salinas, Constanza; Barriga, Kassandra; Albornoz, Alejandro; Alarcon, Pablo; Quiroga, John; Uberti, Benjamín; Sarmiento, José; Henriquez, Claudio; Ehrenfeld, Pamela; Burgos, Rafael A.; Moran, Gabriel (Frontiers in Veterinary Science, 2023)
Neutrophils display an array of biological functions including the formation of neutrophil extracellular traps (NETs), web-like structures specialized in trapping, neutralizing, killing and preventing microbial dissemination within the host. However, NETs contribute to a number of inflammatory pathologies, including severe equine asthma. Tamoxifen (TX) is a selective estrogen receptor modulator which belongs to the triphenylethyllenes group of molecules, and which is used as a treatment in all stages of estrogen-positive human breast cancer. Our previous results suggest that tamoxifen can modulate neutrophil functionality and promote resolution of inflammation; this would partly explain the clinical beneficial effect of this drug in horses with airway inflammation. Enhanced NETs production has been reported with tamoxifen use in humans, but minimal data exists regarding the drug´s effect on NETs in horses. The aim of this study is to assess the in vitro effect of TX on NETs formation from peripheral blood of healthy horses. Five clinically healthy mixed-breed adult horses were enrolled in the study. For this, cellular free DNA quantification, immunofluorescence for the visualization of NETs, assessment of different types of NETs, and detection of mitochondrial superoxide. TX induced NETs formation at a concentration of 10 uM. Our results show that only two types of NETs were induced by TX: 95% spread NETs (sprNETs) and 5% aggregated NETs (aggNETs). Furthermore, induction of these NETs could be influenced by mitochondrial ROS. Future research should involve an in vivo study of horses with severe asthma and TX treatment, to evaluate BALF neutrophil NET formation. In conclusion, this in vitro study suggests that the resolution of inflammation by TX in horses with airway inflammation is due to inhibition of other neutrophilic functions but not to NET formation.